Fabrication of plasma-treated multiwalled carbon nanotube electrodes for detection of quinoline in infected oil palm - Abdul Rahim, Zulaiha (2018)
Oil palms suffer from the major disease, basal stem rot (BSR), caused by the white rot fungus Ganoderma. During the plant-pathogen interactions, secondary metabolites are secreted by plants as defence mechanism. Various types of secondary metabolites secreted being quinoline compound as one of them. A rapid electrochemical technique is developed in order to help in early detection of the disease before the loss of the oil palm plantations. Multiwalled carbon nanotube screen-printed electrode based on Silicon substrate was fabricated for electrochemical sensor. The sensor was applied for the detection of quinoline via linear sweep voltammetry approach. Preliminary study of the growth of multi-wall carbon nanotube (MWCNT) was done using plasma enhanced chemical vapour deposition (PECVD) techniques. Posttreatment of MWCNT using different kinds of plasma atmosphere including oxygen, hydrogen and nitrogen were applied to introduce defects on the surface of MWCNTs and nitrogen plasma gives the most significant arises on the peak current compared to the bare electrode with increment from ~0.33 mA to ~0.52 mA with increased of effective area from ~0.32 cm2 to ~0.49 cm2. The study was further into fabrication of screen-printed electrode system using photolithography methods and the MWCNTs working electrodes were modified under nitrogen plasma to enhance the surface sensitivity. The study was extended into detection of quinoline in secondary metabolite. In pH 7 phosphate buffer saline, an oxidation peak of quinoline was observed. Compared with the unmodified electrode, the NH3-MWCNT modified electrode greatly increases the oxidation peak current of quinoline showing notable enhancement effect. The effects of pH value, amount of MWCNT, accumulation potential and time were studied on the oxidation peak current of quinoline. A detection limit of 0.164μM was also achieved by applying deposition potential of -0.6V and deposition time of 50s. Preliminary study on root extract was done by diluting the extract on 0.1M methanol solution in addition of 0.1M PBS (pH 7) as supporting electrolyte. The linear plot gives an equation of y= 0.4753x-2.2894 with R2= 0.9879.